Carbonation process in lime pastes with different water/binder ratio - Arandigoyen, M.; Álvarez, J. I. (Materiales de Construcción, 2006)
Most research on binder carbonation is based on the analysis of depth changes in the carbonation front. Moreover, previous studies have dealt with mortars, where aggregates play a role in the variations in carbonation patterns. In the approach adopted in the present study, carbonation was determined in terms of the variation in weight resulting from CO2 absorption, and a new parameter (independent of the drying process), denominated A, was established. This parameter was assessed in several lime pastes with different W/B (water/binder) ratios and its variations were correlated to paste microstructure. Due to the type of porosity prevailing in lime pastes, diffusion took place according to Fick's law; water was retained not by capillarity but by surface adsorption. Drying did not retard carbonation in lime pastes